A Comparative Analysis of Chinese and British Consumers’ Consumption Behaviours and Attitudes Toward Fast-Fashion Brand as (Asian Journal of Social Science Studies, 2020)
With emerging of economy and increasing awareness, fast-fashion consumption has been a popular trend around the globe. With features of rapid updating speed, competitive capability and unerring insight, fast-fashion brand consumption had been a regular experience for people in the world. However, owning to different consumption perception and cultural background, attitude towards fast-fashion brands varied from one country to another. Therefore, this research was aimed to conduct a comparative analysis on consumption behavior and attitude about fast-fashion brands between Chinese consumers and British consumers. By means of distributing questionnaires to Chinese consumers and British consumers respectively, this research figured out the similarities and differences in relation to consumption behavior and attitude between Chinese consumers and British consumers. Moreover, major factors were explored to analyze their influence on consumption behavior and attitude of consumers. Finally, with the help of research result and its analysis, effective measures were put forward to help fast-fashion brands to motivate Chinese consumers and British consumers to have fast-fashion brand consumption.